PENGARUH SELF EFFICACY DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN MANHATTAN HOTEL JAKARTA - ELSAY JULIE PRASTICA; Parlagutan Silitonga (Human Capital Development, 2022)
This study aims to analyze the effect of self efficacy and compensation on employee performance. In addition, this study also aims to analyze the effect of job satisfaction mediation variables on the relationship between self efficacy, compensation and employee performance. Data analysis uses the path analysis method with a study population of 100 respondents. The data used in this study are primary data obtained directly from questionnaire answers from employees. The results of the study showed that self efficacy has a positive and significant effect on employee performance, but has no positive and insignificant effect on job satisfaction. Compensation only has a significant effect on employee performance, but has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction is not able to mediate self efficacy with employee performance, but is able to mediate compensation positively and significantly with employee performance.